Risk Factors for Pulmonary Tuberculosis Incidents in the Working Area of the Panyabungan Jae Public Health Center, Mandailing Natal Regency in 2025 - Ahmad Fadil Rangkuti; Sri Siswati; Ratno Widoyo (Universitas Ibn Khaldun Bogor, 2026)
This study aims to analyze risk factors associated with the incidence of Drug-Sensitive Pulmonary Tuberculosis in the Panyabungan Jae Community Health Center (Puskesmas) working area, Panyabungan District, Mandailing Natal Regency. This study was conducted quantitatively with a case-control design. This study included 50 TB patients as cases and 50 non-patients as controls selected using simple random sampling techniques. Data were analyzed using the chi-square test and multiple logistic regression. The results showed that education level, room ventilation, and room lighting were significantly associated with the incidence of Drug-Sensitive Pulmonary TB. Meanwhile, age, gender, smoking status, history of diabetes mellitus, and residential density did not show a significant association. Room lighting was the dominant factor in the incidence of Drug-Sensitive Pulmonary TB. TB transmission is likely due to close contact; poor room lighting increases the probability of contracting Drug-Sensitive TB. Education for TB patients is needed regarding the increased risk of transmission due to poor environmental conditions.